The multi-level governance of formulating regional brand identities: Evidence from three Mega City Regions in China. (May 2020) - Lu, Haiyan; de Jong, Martin; Song, Yun; Zhao, Miaoxi
Abstract: The emergence and expansion of clusters of large metropolitan areas also known as Mega City Regions (MCRs) is a worldwide phenomenon. In China, governmental attempts are made to develop so-called regional brand identities for them. Regional brand identities, as a subspecies of place brand identities, differ from regional identities in the sense that they are the result of conscious branding efforts on the part of public authorities rather than more historically evolved regional identities as experienced by citizens. In this study, the establishment of regional brand identities for three MCRs in China is examined, as these are constituted through and institutionally embedded in intergovernmental relations. We map the perceptions of national, provincial and municipal governments of regional brand identities based on planning documents and relevant interviews. The emergence and stabilization of the regional profiles for China's largest MCRs Pearl River Delta (PRD), Yangtze River Delta (YRD) and Jing-Jin-Ji (JJJ) are featured in their dynamic territorial boundaries, centralized institutionalization and various symbolic meanings. The national government promotes the regional brands to reinforce the strategic awareness and future direction of the region, and these profiles are diffused at the provincial and municipal level. Highlights: Defines regional brand identity as an attractive description or shared understanding of what the region represents. Examined how territorial, symbolic and institutional shapes evolved in the regional brand identity formulation process. Demonstrates how regional brand identity were proposed at the national level and accepted or modified at the lower level. Discusses the transfer possibility for governments to formulate their regional brand identities in developing countries.